Sudan - Toward Sustainable and Broad-Based Growth - World Bank (World Bank, 2012)
Sudan is in the 10th year of its longest and strongest growth episode since independence, benefiting from the advent of oil in 1999. This report proposes a growth strategy for Sudan that reduces its dependence on oil, while building an economic foundation for a diversified, inclusive and sustainable growth path. Specifically, Sudan's near term strategy should focus on: a) developing and maintaining the necessary enabling environment for growth, specifically macroeconomic stability and effective fiscal management (chapter one); b) implementing policies aimed at improving the investment climate and broadening private sector-led growth (chapters two and five); c) increasing returns to the agriculture sector as the highest potential engine of growth and poverty reduction over the medium-term (chapter four); d) developing a comprehensive reconstruction plan for the South (chapter six); and e) complementing technocratic reforms with good governance. Sudan needs a new, more balanced growth vision that is less reliant on oil, while using the oil wealth to create an economic foundation for a diversified, inclusive, and sustainable growth path.